Effect of High-Intensity Interval, Moderate-Intensity Continuous, and Self-Selected Intensity Training on Health and Affective Responses - Oliveira, Gledson Tavares Amorim; Costa, Eduardo Caldas; Santos, Tony Meireles; Bezerra, Ricardo Andrade; Lemos, Telma Maria Araújo Moura; Mortatti, Arnaldo Luis; Elsangedy, Hassan Mohamed (Research quarterly for exercise and sport, 2024)
Purpose: To compare the effects of 12-week high-intensity interval (HIIT), moderate-intensity continuous (MICT), and self-selected intensity training (SSIT) on health outcomes and affective responses. Methods: Seventy-three overweight/obese inactive adults (62% woman; age, 31.4 ± 7.2 years; height, 1.66 ± 0.09 cm; Body mass index, 28.9 ± 2.7 kg.m −2 ) who were randomized into HIIT (n = 23), MICT (n = 24) and SSIT (n = 26) groups. The training was conducted three times per week in an outdoor environment, with 4 weeks under direct supervision and 8 weeks with semi-supervision. Cardiorespiratory fitness, body composition, and metabolic profile were evaluated at baseline and at the end of the 4 th and 12 th weeks. Core affect was measured during all training sessions. Results: Peak oxygen uptake improved in all groups after 4 and 12 weeks compared with baseline. Only the SSIT had reductions in body fat throughout the intervention. No improvements were observed in the metabolic profile across all groups. SSIT was perceived as more pleasurable than HIIT; however, there were no differences in affective responses between SSIT and MICT. Affective responses in-task (e.g. negative and positive peak, rate of change and affect at the end of the exercise session) predicted the HIIT and SSIT exercises attendance rate. Conclusion: Regardless of the exercise training protocol, overweight/obese inactive adults improved health outcomes, which suggests the prescribing HIIT, MICT, and SSIT in outdoor environments. SSIT should be considered in order to optimize the pleasure during training sessions. Affective response more positive in-task of the HIIT and SSIT is associated with greater attendance rate in these exercise protocols.